2014
DOI: 10.1093/mnras/stu2174
|View full text |Cite
|
Sign up to set email alerts
|

The theory of globulettes: candidate precursors of brown dwarfs and free-floating planets in H ii regions

Abstract: Large numbers of small opaque dust clouds -termed 'globulettes' by Gahm et al -have been observed in the H ii regions surrounding young stellar clusters. With masses typically in the planetary (or low mass brown dwarf) regime, these objects are so numerous in some regions (e.g. the Rosette) that, if only a small fraction of them could ultimately collapse, then they would be a very significant source of free floating planets. Here we review the properties of globulettes and present a theoretical framework for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The results obtained by microlensing surveys toward the Galactic Bulge suggest that the frequency of freefloating Jovian planets are 0.25 planets per main-sequence star (Mróz et al 2017). Several dynamical processes have been proposed in order to explain the origin of free-floating planets (FFPs) in our Galaxy: planet-planet scattering (Veras & Raymond 2012), direct formation in grobulettes (Gahm et al 2007;Haworth et al 2015), and the aftermath of evolved stars such as supernova explosions (Veras & Tout 2012).…”
Section: Occurrence Rate Of Free-floating Planetsmentioning
confidence: 99%
“…The results obtained by microlensing surveys toward the Galactic Bulge suggest that the frequency of freefloating Jovian planets are 0.25 planets per main-sequence star (Mróz et al 2017). Several dynamical processes have been proposed in order to explain the origin of free-floating planets (FFPs) in our Galaxy: planet-planet scattering (Veras & Raymond 2012), direct formation in grobulettes (Gahm et al 2007;Haworth et al 2015), and the aftermath of evolved stars such as supernova explosions (Veras & Tout 2012).…”
Section: Occurrence Rate Of Free-floating Planetsmentioning
confidence: 99%
“…Haworth et al (2015) doubt the possibility that the external pressure in the form of radiation or ram pressure can drive globulettes to form brown dwarfs or free-floating planets, and instead they propose the collapse of the globulettes might be triggered by their collisions with the shells that border the expanding H II regions. If Proplyd133-353 was formed in such a globulette near θ 1 Ori C due to either mechanism, we might explain both its younger age (with respect to the one of the ONC) and the lifetime of its disk since its parental cloud can protect it from direct photoevaporation for a timescale of 10 5 -10 6 years (Gahm et al 2007;Haworth et al 2015).…”
Section: The Possible Nature Of Proplyd133-353mentioning
confidence: 99%
“…While the model assumes equilibrium, it is unstable to collapse if sufficiently compressed. Haworth et al (2015) used pressure-bounded BE spheres to model the stability and evolution of small globulettes in Carina cataloged by Grenman & Gahm (2014), including the Tadpole. We revisit the parameters of the Tadpole assuming it is well described by a BE sphere but using the physical parameters we measure with the MUSE data.…”
Section: The Tadpole As a Pressure-boundedmentioning
confidence: 99%
“…If even a small fraction of these globulettes undergo gravitational collapse, they may contribute significantly to the low-mass end of the IMF. However, Haworth et al (2015) showed that these low-mass globulettes are stable and require an additional perturbation to stimulate collapse. Estimated photoevaporation rates (e.g., Smith et al 2004;Reiter et al 2015a) suggest that such small, low-mass objects will be rapidly ablated.…”
Section: Introductionmentioning
confidence: 99%